2014
DOI: 10.1523/jneurosci.1867-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Dependently Activated Cluster of Differentiation 8-Positive T Cells Cause Perforin-Mediated Neurotoxicity in Experimental Stroke

Abstract: Neuroinflammation plays a key role in secondary brain damage after stroke. Although deleterious effects of proinflammatory cytokines are well characterized, direct cytotoxic effects of invading immune cells on the ischemic brain and the importance of their antigendependent activation are essentially unknown. Here we examined the effects of adaptive and innate immune cells-cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells-that share the direct perforin-mediated cytotoxic pathway on outcome after cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 47 publications
7
76
0
Order By: Relevance
“…To determine whether the exacerbation of such injury in GFAP-IL-15 tg mice is mediated by the impact of astrocytic IL-15 on CD8 + T and NK cells, we induced ischemia in WT and GFAP-IL-15 tg mice given anti-CD8 or -NK1.1 mAb 1 d before the induction of MCAO. As reported (32,36,37), CD8…”
Section: Impact Of Cd8 + T and Nk Cells On Ischemic Brain Injury In Gsupporting
confidence: 65%
“…To determine whether the exacerbation of such injury in GFAP-IL-15 tg mice is mediated by the impact of astrocytic IL-15 on CD8 + T and NK cells, we induced ischemia in WT and GFAP-IL-15 tg mice given anti-CD8 or -NK1.1 mAb 1 d before the induction of MCAO. As reported (32,36,37), CD8…”
Section: Impact Of Cd8 + T and Nk Cells On Ischemic Brain Injury In Gsupporting
confidence: 65%
“…Transgenic animals deficient in lymphocytes consistently have smaller infarcts in different stroke models [23][24][25][26]. Moreover, antibody-mediated depletion of CD4 + , CD8 + , and γδ T cells reduced infarct volume and improved functional outcome [25,[27][28][29]. The dynamics of this deleterious role of different proinflammatory T cells have not been fully elucidated.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…Although the majority of studies suggest that T cell populations are deleterious to ischemic stroke outcomes, several studies suggest a more nuanced interpretation of their role 125, 126 . Most studies have found that within the first 24h of ischemic injury, antigen-independent T-cells exert a deleterious effect; this is in contrast to antigen-dependent T-cell responses, which peak 3–7 days after the ischemic insult 127 . CD4+ T-cells are also likely to have deleterious effects, through the secretion of inflammatory cytokines including INF-γ and IL-21 127, 128 .…”
Section: Adaptive Immunity and Strokementioning
confidence: 99%
“…Most studies have found that within the first 24h of ischemic injury, antigen-independent T-cells exert a deleterious effect; this is in contrast to antigen-dependent T-cell responses, which peak 3–7 days after the ischemic insult 127 . CD4+ T-cells are also likely to have deleterious effects, through the secretion of inflammatory cytokines including INF-γ and IL-21 127, 128 . In contrast, CD8+T-cells, through the perforin-granzyme pathway, can cause neuronal cell death and may worsen stroke outcomes 127 .…”
Section: Adaptive Immunity and Strokementioning
confidence: 99%
See 1 more Smart Citation